2019
DOI: 10.1111/sms.13433
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip strength, inflammatory markers, and mortality

Abstract: Purpose To investigate the extent to which inflammatory markers explain the association between handgrip strength and mortality. Methods Analyses of data from The English Longitudinal Study of Ageing. Handgrip strength and inflammatory marker data (C‐reactive protein and fibrinogen) were collected at baseline (2004/5) and inflammatory marker data at follow‐up (2012/13). Participant data were linked with death records. General linear models were used to explore associations between handgrip strength and inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 53 publications
(79 reference statements)
3
33
1
Order By: Relevance
“…The positive association between CC16 and handgrip strength reported in this study is probably because of anti-inflammatory properties of CC16, since systemic inflammation is known to reduce hand-grip strength. 34 We also found an association of serum TSA with FEV 1 % and hand-grip strength. TSA is a marker of inflammation and its serum levels are elevated in systemic inflammation associated with COPD 16 and sarcopenia.…”
Section: Discussionsupporting
confidence: 60%
“…The positive association between CC16 and handgrip strength reported in this study is probably because of anti-inflammatory properties of CC16, since systemic inflammation is known to reduce hand-grip strength. 34 We also found an association of serum TSA with FEV 1 % and hand-grip strength. TSA is a marker of inflammation and its serum levels are elevated in systemic inflammation associated with COPD 16 and sarcopenia.…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, a recent clinical study among hospitalized older patients reported that acute inflammation is associated with decreased muscular strength, mass, and function [31]. In addition, increased chronic inflammation, even at low levels, is associated with adverse metabolic biomarkers, elevated risk of metabolic syndrome, cardiovascular disease, and mortality [29,32,33]. In conjunction, the loss of muscle strength and mass may affect the adverse cardiometabolic health through increased inflammation [26].…”
Section: Discussionmentioning
confidence: 99%
“…More comprehensive evaluations of muscle quality using noninvasive methods in older adults were specifically discussed and highlighted at the multidisciplinary workshop of "Sarcopenia and Physical Performance in Old Age" in 1996 (Dutta et al, 1997). Since then, muscle quality index (MQI) has been recognized as a sensitive surrogate measure of overall health and mortality in the community-dwelling older adults, similarly to strength of quadriceps and hand musculature (Brown et al, 2016;McGregor et al, 2014;Newman et al, 2006;Park et al, 2006;Rijk et al, 2016;Smith et al, 2019;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%